EFFECT OF SEED SIZE ON SEEDLING VIGOR AND SEED YIELD IN VEGETABLE SEED PRODUCTION: A REVIEW - Esraa Abd-alhuseein Jasim; Kamal benyamin Esho (European Journal of Agricultural and Rural Education, 2022)
Seed size influences vegetative growth and is frequently linked to yield. Market circumstances and the harvest’s success Seed size varies between species due to genetic variability. Extra-large, large, medium, small, and extra small are the five seed sizes available. This variation is caused by the passage of nutrients through the seed in the mother plant. Food reserves are accumulated later because the seed coat and embryonic axis mature first in the seed inside the capsule. The filling of food stores for later seedling growth is affected by this size disparity. In various crop varieties, seed size has been proven to have a variety of effects on seed germination, emergence, and other agronomic aspects. In the field, broad seeds perform better than microscopic seeds.